Tort law in Germany - Spindler, Gerald (Kluwer Law International, 2019)
Derived from the multi-volume 'International Encyclopaedia of Laws', this book provides ready access to how the legal dimension of prevention against harm and loss allocation is treated in Germany. This traditional branch of law not only tackles questions which concern every lawyer, whatever his legal expertise, but also concerns each person?s most fundamental rights on a worldwide scale.00Following a general introduction that probes the distinction between tort and crime and the relationship between tort and contract, the monograph describes how the concepts of fault and unlawfulness, and of duty of care and negligence, are dealt with in both the legislature and the courts. The book then proceeds to cover specific cases of liability, such as professional liability, liability of public bodies, abuse of rights, injury to reputation and privacy, vicarious liability, liability of parents and teachers, liability for handicapped persons, product liability, environmental liability, and liability connected with road and traffic accidents. Principles of causation, grounds of justification, limitations on recovery, assessment of damages and compensation, and the role of private insurance and social security are all closely considered.